Effects of exercise on cardiac autonomic modulation in children: literature update - Gustavo Henrique de Oliveira Mondoni; Luiz Carlos Marques Vanderlei; Bruno Saraiva; Franciele Marques Vanderlei
AbstractIntroduction It is known that physical exercise is beneficial and precipitates adjustments to the autonomic nervous system. However, the effect of exercise on cardiac autonomic modulation in children, despite its importance, is poorly investigated.Objective To bring together current information about the effects of exercise on heart rate variability in healthy and obese children.Methods The literature update was performed through a search for articles in the following databases; PubMed, PEDro, SciELO and Lilacs, using the descriptors "exercise" and "child" in conjunction with the descriptors "autonomic nervous system", "sympathetic nervous system", "parasympathetic nervous system" and also with no descriptor, but the key word of this study, "heart rate variability", from January 2005 to December 2012.Results After removal of items that did not fit the subject of the study, a total of 9 articles were selected, 5 with healthy and 4 with obese children.Conclusion The findings suggest that exercise can act in the normalization of existing alterations in the autonomic nervous system of obese children, as well as serve as a preventative factor in healthy children, enabling healthy development of the autonomic nervous system until the child reaches adulthood.